1996
DOI: 10.1159/000157391
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Myelopathy in Kuwait: A Report of 2 Patients and Review of Possible Links

Abstract: The clinical and radiological features of 2 patients with HTLV-1 myelopathy are presented. The mother of 1 patient is a carrier. This is the first report of HTLV-1 infection from Kuwait and the Arabian Peninsula. Both patients were traced to Najaf, a town south of Bagdad in Iraq. Other Middle East cases were reviewed and suggest both a common source and a strong link to our cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Later it has been shown that the high prevalence of HTLV-I infection is also characteristic for the Muslim population of Mashhad [23]. The cases of HTLV-I infection and HTLV-I-associated diseases were also described in Iraq [24] and, recently, in Kuwait [25,26]. After that several more cases of HAM/TSP and 2 cases of ATTL have been diagnosed in Kuwait [27, unpublished].…”
Section: Discussionmentioning
confidence: 99%
“…Later it has been shown that the high prevalence of HTLV-I infection is also characteristic for the Muslim population of Mashhad [23]. The cases of HTLV-I infection and HTLV-I-associated diseases were also described in Iraq [24] and, recently, in Kuwait [25,26]. After that several more cases of HAM/TSP and 2 cases of ATTL have been diagnosed in Kuwait [27, unpublished].…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-I was also described in Iraq, southern region of which had close historical ties with Mashhad; the latter is a holy city for Shiite Muslims and southern Iraq is populated mainly by Shiites. HTLV-I was also described in Kuwait, again in the families originating from southern Iraq and specifically from the city of Najaf which for centuries had close ties with Mashhad [Voevodin et al, 1995;Farah et al, 1996]. Thus, the pattern had been emerging suggesting that a cluster of HTLV-I infection in the Mashhadi Jews is not an isolated one, but just one of the ''derivatives'' of the same lineage of cosmopolitan HTLV-I which had spread throughout the Middle East from Mashhad.…”
Section: Discussionmentioning
confidence: 97%
“…Later, it was also shown that the high prevalence of HTLV-I infection is also characteristic of the Muslim population of Mashhad [Kitze et al, 1992;Gabarre et al, 1993;Vidal et al, 1994;PuccioniSohler et al, 1995;Safai et al, 1996, Farid et al, 1995. Cases of HTLV-I infection and HTLV-I-associated diseases have also been described in Iraq [Denic et al, 1990] and, recently, in Kuwait [Voevodin et al, 1995;Farah et al, 1996;Al-Mufti et al, 1996].…”
Section: Introductionmentioning
confidence: 97%
“…Also, no Saudi donor had tested positive in previous studies, 17,18 except for nine samples which tested positive by WB from 33,908 Saudi donors screened in the Eastern Province, which has a low prevalence rate of 0.022%. 19 The majority of EIA-reactive results 14,19 were indeterminate by Western blot. The samples tested again by WB still gave the same results.…”
Section: Discussionmentioning
confidence: 99%
“…11 HTLV-I is now recognized to occur worldwide, although it is characteristically endemic in Japan, the Caribbean, Southern Italy, New Guinea, Africa, and the Seychelles, 12 as well as in several countries in the Middle East. [13][14] In the present study, we took sera from volunteer Saudi blood donors and hemodialysis patients over a threeyear period to determine the prevalence of HTLV-I/II among Saudi blood donors, and to examine the cost effectiveness of HTLV screening in Saudi blood banks.…”
mentioning
confidence: 99%